2005
DOI: 10.1093/eurheartj/ehi350
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the genesis and perpetuation of atrial fibrillation

Abstract: The prevalence and persistence of atrial fibrillation (AF) and the relative inefficacy of the currently available pharmacotherapy requires development of new treatment strategies. Recent findings have suggested a mechanistic link between inflammatory processes and the development of AF. Epidemiological studies have shown an association between C-reactive protein and both the presence of AF and the risk of developing future AF. In case-control studies, C-reactive protein is significantly elevated in AF patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
289
0
21

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(314 citation statements)
references
References 69 publications
4
289
0
21
Order By: Relevance
“…Recent studies indicate a mechanistic link between the inflammatory processes and the development of AF. 31,32 Frustaci et al first demonstrated a high prevalence of inflammatory infiltrates, myocyte necrosis and fibrosis in atrial biopsies from patients with lone AF, but not in atrial biopsies from control patients. 33 Other papers have reported that an increase in high-sensitivity C-reactive protein levels is an independent risk factor for future AF among patients with sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate a mechanistic link between the inflammatory processes and the development of AF. 31,32 Frustaci et al first demonstrated a high prevalence of inflammatory infiltrates, myocyte necrosis and fibrosis in atrial biopsies from patients with lone AF, but not in atrial biopsies from control patients. 33 Other papers have reported that an increase in high-sensitivity C-reactive protein levels is an independent risk factor for future AF among patients with sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…26 Inflammatory changes have been observed in atrial tissues obtained from patients with isolated persistent AF. 27 Serum CRP level has been found to be significantly higher in patients with paroxysmal and chronic AF than in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…29 Atrial damage may trigger a lowgrade inflammatory response and be part of a structural remodeling with increased persistence of AF. 26 Dernellis et al showed that complements increase the CRP-related incidence of AF in apparently healthy subjects with normal sinus rhythm. 30 Also in this study, no significant relation was found between a high CRP level and AF in the absence of elevated complement components.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Furthermore, Cardin et al 25 were able to demonstrate increased atrial expression of angiotensin II is linked with increased atrial cell death and leukocyte infiltration, again supporting a potential link between the RAAS, inflammation and AF.…”
Section: Electrical Remodellingmentioning
confidence: 94%
“…10 The RAAS, inflammation and AF There is accumulating evidence (from genetic studies, quantification of established inflammatory markers and histological sampling) pointing to an important association between inflammation and AF. 26 While a detailed synopsis of this putative link is beyond the scope of this commentary, there is evidence to date in support of a role for RAAS activation as an important factor in this association.…”
Section: Electrical Remodellingmentioning
confidence: 99%